Evaluation of water-stress tolerance in soybean using NDVI, gas exchange and morphological traits: EVALUATION OF WATER-STRESS TOLERANCE IN SOYBEAN - S R MUNDHE; S A JAYBHAY; R M PATIL; PHILIPS VARGHESE; D H SALUNKHE; B D IDHOL; B N WAGHMARE (Journal of Oilseeds Research, 2021)
A field experiment was conducted during 2017 and 2018 under drought stress (DS) and non-stress conditions (IR) to identify drought tolerant soybean accessions as well as agronomic and physiological traits contributing to drought stress tolerance. Sixty-four soybean accessions including released varieties, genetic stocks and five check varieties were sown in an augmented design. The traits contributing to total biomass viz., plant height, number of pods, number of branches, shoot-root dry weight at vegetative stage, and NDVI at vegetative as well as pod filling stage were associated with water-stress tolerance in soybean. Physiological traits viz., relative leaf water content (RWC), normalized vegetative index (NDVI) and chlorophyll index were higher in non-stressed crop. Similarly, higher activities ofthe gas exchange traits viz., photosynthetic rate (Pn), stomata conductance (Gs), intercellular CO2 concentration (Ci) and transpiration rate (Tr) were observed under non stress condition. On the basis of minimum yield reduction under stress and drought tolerance indices the soybean accessions RSC 10-46, TAMS 98-21, EC 241780, MACS 1281, HARDEE, MAUS 612, DS 9814, MACS 1460 and KDS 753 were observed as water stress tolerant while, EC 241695, LEE 54, MACS 1370, CAT 3466, PK 1029, VLS 75, AGS 228 and AMS 1002 were observed as water stress sensitive. These findings were confirmed by the cumulative rank due to drought tolerance indices such as stress susceptibility index (SSI), stress tolerance index (STI), tolerance (TOL), yield index (YI), drought resistance index (DRI), yield stability index (YSI), stress susceptibility percentage (SSPI), drought tolerance efficiency (DTE) and modified stress tolerance index (MSTI) as well as cluster analysis using drought tolerance indices, hence, could be useful in soybean improvement for water-stress tolerance.